Nature - Wogram, Nils 1972- ('edel'records, 2014)
Der deutsche Posaunist spielt mit seinem Trio besten Modern Jazz, gleichermaßen tiefgründig wie entspannt.
Solitude. Hofstetten. The trail. Birds. Uncultivated land. As wave follows wave. Sanctuary. Quiet river. Village for sale. Dipper
Keywords: CD